CASH HOLDINGS AS A FINANCIAL RISK MANAGEMENT INSTRUMENT: EMPIRICAL EVIDENCE FROM THE HEALTHCARE INDUSTRY IN DEVELOPING COUNTRIES DURING COVID-19 - Bulan Nettiary Kelara (TECHNOBIZ : International Journal of Business, 2026)
This study examines cash holdings as a financial risk management instrument in the healthcare industry of developing countries during the COVID-19 pandemic. Using a quantitative approach, the study analyzes healthcare firms listed in Indonesia, Malaysia, Thailand, and Vietnam, with samples selected through purposive sampling. The data are analyzed using stepwise linear regression with panel data techniques and processed using EViews 13. The findings indicate that financial constraints negatively affect cash holdings only in Malaysia, while no significant effect is observed in Indonesia, Thailand, and Vietnam. Financial leverage does not significantly influence cash holdings in any of the countries studied. Profitability positively affects cash holdings in Indonesia and Malaysia, negatively affects cash holdings in Thailand, and has no significant effect in Vietnam. Growth opportunities have a positive effect on cash holdings only in Thailand, while no significant effect is found in the other countries. These results suggest that cash holding policies function as a context-dependent financial risk management mechanism, shaped by country-specific financial conditions, institutional environments, and crisis responses. This study contributes to the literature by providing empirical evidence from the healthcare sector, which remains underexplored in cash holding and risk management research, particularly in the context of global uncertainty following the COVID-19 pandemic. The findings also highlight the importance of locally tailored financial risk management strategies for firms and policymakers in the healthcare sector across ASEAN countries.